Best Approximation in Cone-Normed Space - Abdallah Hakawati; Sawsan Al-Dwaik (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The question of whether cone metric spaces are real generalizations of metric spaces is proved, in the sense of Best Approximation, not to be affirmative.